"STUDENT'S SOCIO-EMOTIONAL AND ACADEMIC ADJUSTMENTS DURING COVID 19" - Nirupama Prakash; Vijay Kulkarni (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
A record-breaking 1.1 billion children have dropped out of school owing to COVID-19 pandemic. Various measures are being taken by governments globally to help minimise the impact of the pandemic resulting from closure of schools and colleges; a disruption of the the conventional schooling. It is also observed that all nations are in the midst of the most severe economic crises we have ever wittnessed, placing immense pressure on government budgets and personal incomes.The biggest sufferers were the students who had to adapt to the newly evolved virtual space in education. Transition from conventional modes of education, that is face to face in a physical classroom to virtual platform demanded immediate technology adaption.An extensive study of the adjustments and challenges faced by the students is important inorder to help the students to experience a smooth transition.A sample of 250 individuals was randomly chosen from ten higher secondary schools using the descriptive survey research technique. The research found that there is a favorable and substantial connection between social and emotional adjustment and academic performance of students and that Socio-emotional skill have to be enhanced to improve academic performance.